2017
DOI: 10.1007/s00428-017-2102-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Rsf-1 correlates with poor survival and promotes invasion in non-small cell lung cancer

Abstract: Rsf-1 (HBXAP) was recently reported to play roles in tumorigenesis and tumor progression. There have been many reports referred to Rsf-1 overexpression in various cancers and associated with the malignant behavior of cancer cells. However, the molecular mechanism of Rsf-1 in non-small cell lung cancer aggressiveness remains ambiguous. In the present study, we found that there was a significant association between Rsf-1 overexpression and poor overall survival (p = 0.028) in lung cancer. Furthermore, knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 20 publications
5
17
0
Order By: Relevance
“…The results, suggesting that high RSF1 expression indicates a poor prognosis of RCC, are consistent with data in ovarian, prostate and hepatocellular cancer (17,18,21). The results may be explained by previous studies demonstrating that RSF1 promotes tumor cell proliferation and invasion (10,13,14,16). All of these results together suggest that RSF1 is an important oncogene in RCC.…”
Section: Event-free Survivalsupporting
confidence: 90%
See 3 more Smart Citations
“…The results, suggesting that high RSF1 expression indicates a poor prognosis of RCC, are consistent with data in ovarian, prostate and hepatocellular cancer (17,18,21). The results may be explained by previous studies demonstrating that RSF1 promotes tumor cell proliferation and invasion (10,13,14,16). All of these results together suggest that RSF1 is an important oncogene in RCC.…”
Section: Event-free Survivalsupporting
confidence: 90%
“…The genes of the region include RSF1, EMSY, BRCA2 interacting transcriptional repressor, P21 (RAC1) activated kinase 1 (PAK1), RAD9 checkpoint clamp component A, and cyclin D1 have been proposed as candidate tumor driver genes (12,13,15,(23)(24)(25)(26). Numerous studies have demonstrated that the amplification of RSF1 is not only significantly correlated with tumor cell proliferation, migration, invasion and apoptosis abilities, but also with poor prognosis of patients with ovarian, lung, hepatocellular and prostate cancer (14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rsf-1 encodes a histone-binding protein named remodeling and spacing factor 1 (Rsf-1), which was found to interact with human sucrose nonfermenting protein 2 homologue (hSNF2H) to form an ISWI chromatin remodeling complex [8], which is involved in chromatin remodeling and transcriptional regulation [9]. Rsf-1 is amplified and/or overexpressed in various cancers, including ovarian [7, 8], breast [10], bladder [11], esophageal [12], lung [13], colon [14], and head and neck cancers [15]. Elevated levels of Rsf-1 are correlated with poor prognosis [16].…”
Section: Introductionmentioning
confidence: 99%